Feasibility of mK-line and mSC-line in segments choice for laminoplasty of multilevel cervical spondylotic myelopathy - Cui, Zhiming; Wu, Bo; Xu, Guanhua; Chen, Jiajia; Zhang, Jinlong; Wang, Lingling; Li, Weidong; Hong, Hongxiang; Wu, Chunshuai (Frontiers in Surgery, 2025)
ObjectivesLaminoplasty (LAMP) is a common procedure for multilevel cervical spondylotic myelopathy (MCSM). The traditional K-line is a guide for LAMP candidate selection but is inferior to the modified K-line (mK-line) in predicting clinical outcomes. The spinal cord line (SC-line) is another indicator that considers anterior compression but is not typically used for selecting surgical segments. This study intended to propose and validate the combined application of modified spinal cord line (mSC-line) with mK-line for surgical decision-making in MCSM patients.MethodsThis study included 63 MCSM patients categorized into K-line(−) group and K-line(+) group, or Type I group and Type II group based on SC-line. We defined mK-line and mSC-line in sagittal T2WI MRIs. All patients with both mK-line(+) and mSC-line(+) underwent standard LAMP. Radiographic analysis was conducted using CCI, mK-INT and mSC-INT. Clinical outcomes were evaluated by JOA, NDI and VAS scores. Preoperative and postoperative radiological outcomes and clinical outcomes were used to evaluate the prognosis and the efficacy of segmental decision-making.ResultsThere were no difference in baseline characteristics among all the participants. Post-operative spinal cord shift indicators (mK-INT and mSC-INT) increased significantly. The JOA score increased, while NDI and VAS scores decreased. Both the radiological outcomes and clinical outcomes demonstrated a good prognosis even in K-line(−) group and Type II group. There was a statistical correlation between JOA score recovery rate with both mK-INT and mSC-INT.ConclusionsThe presence of mK-line(+) and mSC-line(+) in MRI is crucial for the selection of surgical segments in LAMP for MCSM patients. This combined criterion can help predict sufficient decompression of the cervical spinal cord and good clinical outcomes.